2010
DOI: 10.4236/jbise.2010.34054
|View full text |Cite
|
Sign up to set email alerts
|

Classification of human emotion from EEG using discrete wavelet transform

Abstract: In this paper, we summarize the human emotion recognition using different set of electroencephalogram (EEG) channels using discrete wavelet transform. An audio-visual induction based protocol has been designed with more dynamic emotional content for inducing discrete emotions (disgust, happy, surprise, fear and neutral). EEG signals are collected using 64 electrodes from 20 subjects and are placed over the entire scalp using International 10-10 system. The raw EEG signals are preprocessed using Surface Laplaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
161
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(170 citation statements)
references
References 15 publications
0
161
0
3
Order By: Relevance
“…The joint highly time-frequency resolution, which cannot be achieved by either Fast Fourier Transform (FFT) or by Short Time Fourier Transform (STFT), obtained by wavelet transform yields a more reliable candidate for the extraction of potential features in EEG [15]. In the proposed approach, we employ the Mallat algorithm [16] to obtain the multi-resolution wavelet decomposition of EEG.…”
Section: 2wavelet-cspmentioning
confidence: 99%
“…The joint highly time-frequency resolution, which cannot be achieved by either Fast Fourier Transform (FFT) or by Short Time Fourier Transform (STFT), obtained by wavelet transform yields a more reliable candidate for the extraction of potential features in EEG [15]. In the proposed approach, we employ the Mallat algorithm [16] to obtain the multi-resolution wavelet decomposition of EEG.…”
Section: 2wavelet-cspmentioning
confidence: 99%
“…Nevertheless, through the feature selection process, some researchers have found that other EEG channels were better suited for emotion recognition [20,21]. In the frequency domain, particular emotions are believed to affect specific frequency bands, such as alpha [22,23], gamma [24,25] and theta [26], and some researchers have incorporated all frequencies, delta, alpha, beta, theta and gamma [19,27], into their EEG research. In this work, we used all frequencies of brain signals and omitted none.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Silberstein [21] have focused on external effects on human emotions using EEG measurements for determining the level of attention of a subject to a visual stimulus. Murugappan et al [17] classified dynamic emotional content into five discrete emotions (disgust, happy, surprise, fear and neutral) based on Electroencephalography (EEG) signal. Recently, EEG-based emotion recognition using deep learning network with principal component improved classification accuracy compared to SVM and naïve Bayes classifier [12].…”
Section: 2mentioning
confidence: 99%